Spectroscopic, structural and computational analysis of [Re(CO)3(dippM)Br]n+ (dippM = 1, 1′-bis(diiso-propylphosphino)metallocene, M = Fe, n = 0 or 1; M = Co, n = 1). Issue 11 (12th February 2016) - Furneaux, Aliza G.; Piro, Nicholas A.; Hernández Sánchez, Raúl; Gramigna, Kathryn M.; Fey, Natalie; Robinson, Michael J.; Kassel, W. Scott; Nataro, Chip
Abstract : [Re(CO)3 (dippf)Br] + : the first structurally characterized complex of a coordinated bis(phosphino)ferrocenium ligand. Abstract : While the redox active backbone of bis(phosphino)ferrocene ligands is often cited as an important feature of these ligands in catalytic studies, the structural parameters of oxidized bis(phosphino)ferrocene ligands have not been thoroughly studied. The reaction of [Re(CO)3 (dippf)Br] (dippf = 1, 1′-bis(diiso-propylphosphino)ferrocene) and [NO][BF4 ] in methylene chloride yields the oxidized compound, [Re(CO)3 (dippf)Br][BF4 ]. The oxidized species, [Re(CO)3 (dippf)Br][BF4 ], and the neutral species, [Re(CO)3 (dippf)Br], are compared using X-ray crystallography, cyclic voltammetry, visible spectroscopy, IR spectroscopy and zero-field 57 Fe Mössbauer spectroscopy. In addition, the magnetic moment of the paramagnetic [Re(CO)3 (dippf)Br][BF4 ] was measured in the solid state using SQUID magnetometry and in solution by the Evans method. The electron transfer reaction of [Re(CO)3 (dippf)Br][BF4 ] with acetylferrocene was also examined. For additional comparison, the cationic compound, [Re(CO)3 (dippc)Br][PF6 ] (dippc = 1, 1′-bis(diiso-propylphosphino)cobaltocenium), was prepared and characterized by cyclic voltammetry, X-ray crystallography, and NMR, IR and visible spectroscopies. Finally, DFT was employed to examine the oxidized dippf ligand and the oxidized rhenium complex, [Re(CO)3 (dippf)Br] + .